Analisis Strategi Manajemen Klaim dalam Menekan Risiko Fraud Asuransi Kesehatan: Analisis Systematic Literature Review - Rahmi, Safirina Aulia; Wahno; Tiara Asyfia Sidik (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
The National Health Insurance (JKN) program in Indonesia is designed to ensure equitable access to healthcare services for all citizens. However, fraud within the health insurance claim process remains a critical challenge, posing financial risks to the state and undermining public trust in the system. This study aims to analyze claim management strategies for mitigating fraud risk using a systematic literature review (SLR) approach. Literature was sourced from Google Scholar and Semantic Scholar, selected through the PRISMA method, and evaluated using a standardized quality assessment framework. The analysis reveals that key challenges include weak administrative verification, inaccurate coding, and a lack of system integration between hospitals and BPJS. Preventive strategies such as strengthening internal governance, digitizing medical records, enhancing staff competence, and implementing risk governance principles have proven effective in building a more accountable and resilient claim management system.